The effect of thermal modification of turbostratic carbon on its fractal structure - Mandzyuk, V.I.; Lisovskiy, R.P.; Kulyk, Yu.O.; Rachiy, B.I.; Solomovskyi, R.V. (Physics and Chemistry of Solid State, 2024)
Fractal structure of porous carbon materials (PCMs) obtained by thermal modification under different regimes was investigated using the method of low-temperature porometry. It was established that at modification temperatures of 300 and 600°C, materials with a developed microporous structure are formed, the surface fractal dimension of which is 2.6. At modification temperatures of 400 and 500°C, the value of the fractal dimension of the surface decreases to a value of 2.22, which indicates the formation of an almost smooth surface due to the intensive removal of carbon atoms from the near-surface layers of the material particles, a decrease in the number of micropores with their transition into mesopores, unification of small carbon clusters into larger ones and the formation of microparticles of non-porous carbon material.